ORDER, ANARCHY, AND INQUIRY IN EDUCATIONAL ADMINISTRATION - Ryan, James (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1995)
ABSTRACT. This article explores future prospects for inquiry in educational administration. In particular it looks at efforts to bring conceptual order to often unorderly school organizations. lt is argued that the pace and nature of our changing world and the increasing impact of diversity will erode the legitimacy of approaches that look to establish underlying and enduring patterns of human interaction in schools. This is done by illustrating how the process of theory construction works with the help of a piece of popular fiction, describing the rapidly changing contemporary experience of space and time, and showing how the increasing acceptance of diversity is influencing theory construction. Finally, the author offers a number of suggestions for future inquiry. RÉSUMÉ. Cet article examine les perspectives de recherche en administration scolaire. L’auteur s’attarde en particulier aux efforts déployées pour imposer un ordre conceptuel aux organismes scolaires où règne souvent le désordre. L’auteur soutient que le rythme et la nature du monde mouvant où nous vivons et l’impact croissant de la diversité auront pour effet d’éroder la légitimité des approches qui visent à établir des structures sous-jacentes d’interaction humaine durables dans les écoles. Pour ce faire, l’auteur illustre à partir d’une fiction populaire le fonctionnement du processus d’élaboration des théories, décrit l’expérience contemporaine très mouvante de l’espace et du temps et montre comment l’acceptation de plus en plus grande de la diversité influence l’élaboration des théories. Enfin, l’auteur propose un certain nombre de pistes de recherche.